Biosynthesis of Δ-aminolevulinate in greening barley leaves. VI. Activation of glutamate by ligation of RNA - Kannangara, C.; Gough, S.; Oliver, Richard; Rasmussen, S. (1984)
The components involved in the enzymic conversion of glutamate to δ-aminolevulinate have been separated into three fractions; a Blue Sepharose bound, a chlorophyllin-(or heme) Sepharose bound and an unbound fraction. Combination of these three fractions reconstituted δ-aminolevulinate synthesis from glutamate. Participation of a specific RNA in δ-aminolevulinate synthesis was established by isolating a homogeneous RNA from the chlorophyllin-Sepharose bound fraction and reconstituting δ-aminolevulinate synthesis in the presence of the unbound and Blue Sepharose bound fractions. The RNA involved in δ-aminolevulinate synthesis was purified by high-pressure liquid chromatography and preparative gel electrophoresis. In the presence of the Blue Sepharose bound fraction, ATP and Mg2+, glutamate bound covalently to this RNA. Co(III)-ATP-o-phenanthroline bound to the RNA and strongly inhibited glutamyl-RNA formation, whereas heme and Mg-protoporphyrin at 50 μM were only slightly inhibitory. The chlorophyllin-Sepharose bound fraction also contained two other glutamate acceptor RNAs. RNAase A and snake venom phosphodiesterase strongly reduced δ-aminolevulinate synthesis and glutamyl-RNA formation, whereas addition of DNAase or spleen phosphodiesterase was only slightly inhibitory. The RNA became sensitive to the spleen enzyme after phenol extraction of the chlorophyllin-Sepharose bound fraction. E. coli tRNAGlu orwheat germ tRNA did not reconstitute δ-aminolevulinate synthesis when combined with the Blue Sepharose bound and unbound fractions. The RNA involved in δ-aminolevulinate synthesis hybridised to a 3.9 kb Hind III Pst I restriction endonuclease fragment from the barley chloroplast genome located in the large single copy region 38 kb from the large subunit gene for RuBP carboxylase and 12 kb from the inverted repeats. Glutamate 1-semialdehyde aminotransferase was labelled during35S-incorporation into greening barley leaves but not during incorporation into isolated plastids. It is suggested that an NADPH-dependent dehydrogenase involved in the reduction of glutamyl-RNA to glutamate 1-semialdehyde is present in the Blue Sepharose bound fraction.